2013
DOI: 10.3727/096368912x662381
|View full text |Cite
|
Sign up to set email alerts
|

Technique of Endoscopic Biopsy of Islet Allografts Transplanted into the Gastric Submucosal Space in Pigs

Abstract: Currently, islet cells are transplanted into the liver via portal vein infusion. One disadvantage of this approach is that it is not possible to adequately biopsy the islets in the liver to assess for rejection. Islet Tx into the gastric submucosal space (GSMS) can be performed endoscopically, and has the potential advantage of histological evaluation by endoscopic biopsy. The aim of this study was to determine whether a representative allograft sample could be obtained endoscopically. We performed islet Tx in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 44 publications
0
31
0
1
Order By: Relevance
“…We previously established the technique of endoscopic biopsy after islet transplantation into the GSMS in non-diabetic pigs not receiving immunosuppressive therapy. 5 Tissue obtained at both biopsy and necropsy 5 d after transplantation showed similar histological features of rejection. These results indicated that endoscopic biopsy of islet allografts in the GSMS is feasible, and provides accurate histopathological data.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…We previously established the technique of endoscopic biopsy after islet transplantation into the GSMS in non-diabetic pigs not receiving immunosuppressive therapy. 5 Tissue obtained at both biopsy and necropsy 5 d after transplantation showed similar histological features of rejection. These results indicated that endoscopic biopsy of islet allografts in the GSMS is feasible, and provides accurate histopathological data.…”
Section: Introductionmentioning
confidence: 78%
“…Under inhalational anesthesia, islets (in culture medium C/¡ 17 mM BMX-001) were transplanted into the GSMS at 4 (Group1) or 7 (Group2) sites endoscopically via submucosal injection (GIF-2T160, Olympus Medical Systems, Center Valley, PA). 5…”
Section: Endoscopic Islet Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…Overcoming this barrier is proving difficult, although genetic modification of the pigs may prove helpful [61]. An alternative would be the transplantation of the islets in sites other than the liver, such as the gastric submucosal space, where the islets are not immediately exposed directly to blood, but still receive a good supply of oxygen and nutrients [62,63]. An ideal site should feature portal delivery of insulin, but be accessible by a minimally-invasive procedure associated with minimal complications.…”
Section: Pig-to-primate Cell Transplantationmentioning
confidence: 99%
“…This study showed that the striated muscle could be a promising site for islet transplantation that promotes full revascularization of Curr Radiol Rep (2013) 1:205-215 209 implanted grafts. Besides the forearm muscle, several other islet transplantation sites including the gastric submucosal space [80,81] and adrenal glands [82] have also been investigated. Clearly, non-invasive imaging could greatly assist in evaluating these sites and in monitoring islet survival aiding to clinical translation of these new approaches.…”
Section: Mri Tracking Of Transplanted Isletsmentioning
confidence: 99%